PENDAMPINGAN PENYUSUNAN BLUE PRINT/ROAD MAP KAMPUNG AIRPORT SEBAGAI KAMPUNG WISATA - Shofwatun (LPPM Universitas Insan Pembangunan, 2023)
This activity was carried out in Airport Village, Teluk Naga District, Tangerang Regency. The hope of the activists from this village is to make the Airport village known for its culinary tourism and creative economy for the sake of the economic independence sustainability for all its residents. The basic problem of this village is that there is no preparation of a blue print/road map for the establishment of this tourism icon, which includes goals, targets, strategies and business implementation to help in submitting funds to the local government and private agencies. This blue print is important for the further development of the village according to the planning of the tourist village that all the residents dream of. The preparation of a blue print/road map for this village is an initial solution that will be done as an effort to create a tourist village. This blue print/road map will clearly describe how much is the estimated Budget Plan for the tourist object that will be worked on, where the object includes the construction of the water channel/sewer design at the edge of the village, the construction of signboards/village entrance signs, and improvements village order. Kegiatan pengabdian kepada masyarakat ini dilakukan di Kampung Airport Kecamatan Teluk Naga Kabupaten Tangerang. Harapan dari penggiat dari kampung ini adalah ingin membuat kampung Airport dikenal dengan tempat wisata kuliner dan ekonomi kreatif demi keberlanjutan kemandirian ekonomi seluruh warganya. Permasalahan mendasar dari kampung ini adalah belum adanya penyusunan blue print/ road map untuk penetapan ikon wisata ini, yang meliputi tujuan, sasaran, strategi dan implementasi bisnis guna membantu dalam pengajuan dana ke pemerintah daerah maupun instansi-instansi swasta. Blue print ini penting untuk pembangunan kampung lebih lanjut sesuai perencanaan kampung wisata yang diimpikan semua warganya. Penyusunan blue print/ road map untuk kampung ini merupakan solusi awal yang akan dikerjakan sebagai upaya mewujudkan kampung wisata. Blue print/ road map ini akan menggambarkan dengan jelas berapa kira-kira Rencana Anggaran Biaya (RAB) untuk objek wisata yang akan digarap, dimana objek tersebut meliputi pembangunan desain saluran air/selokan di tepi kampung, pembangunan plang/tanda masuk kampung, dan perbaikan tatanan kampung. Kata Kunci : Blue Print, Road Map, Wisata.